2022
DOI: 10.3390/jcm11123308
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Fatigue Performance of Patient-Specific Polymer Plates in Oncologic Mandible Reconstruction

Abstract: Mandible defects are conventionally reconstructed using titanium plates. However, titanium causes metallic artifacts which impair radiological imaging. This study aims at evaluating mechanical fatigue of radiolucent fiber-reinforced polyetheretherketone (f-PEEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyphenylsulfone (PPSU) polymer plates for mandible reconstruction. A total of 30 plates (titanium [n = 6], f-PEEK [n = 6], PEEK [n = 6], PEKK [n = 6], PPSU [n = 6]) were implanted in syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In terms of orbital PSIs, the implants are planned mirroring the other, healthy, orbit. The gold standard material for PSIs remains titanium, but other materials such as PEEK (Polyetheretherketone) have recently been introduced [ 4 , 5 ]. During the usual manufacturing process, titanium patient-specific implants are machine polished.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of orbital PSIs, the implants are planned mirroring the other, healthy, orbit. The gold standard material for PSIs remains titanium, but other materials such as PEEK (Polyetheretherketone) have recently been introduced [ 4 , 5 ]. During the usual manufacturing process, titanium patient-specific implants are machine polished.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, radiolucent polymer mandible reconstruction plates consisting of polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyphenylsulfone (PPSU) and polyethylene (PE) were found to significantly reduce streak and blooming artifacts in CT images compared to titanium [ 15 ]. In an ensuing investigation, it was shown that PEEK, fiber enforced PEEK (f-PEEK) and PEKK provide sufficient fatigue strength to withstand chewing cycles over the cause of at least one year after segmental mandibulectomy [ 16 ]. While these are promising results for mandible reconstruction, there are almost no studies analyzing the radiological effects of polymer plates for midfacial reconstruction.…”
Section: Introductionmentioning
confidence: 99%